Optimizing The Role of Pokdarwis in Ecotourism Management in Karang Sidemen Village, Central Lombok Regency, Indonesia - Triony, Triony Septia Susana Sarahel Peni; Uwi Martayadi (Faculty of Economics and Business, University of Mataram, 2022)
One of the villages that has developed the ecotourism concept is Karang Sidemen Village, North Batukliang District, Central Lombok Regency, West Nusa Tenggara. The destinations in Karang Sidemen Village are managed by the Selendang Biru Rinjani Tourism Awareness Group (Pokdarwis). This Pokdarwis has been active since 2018. Pokdarwis in its function as a subject or community actor has a role and responsibility to jointly encourage the success of tourism management in Karang Sidemen Village which is now a pilot tourism village. However, the quality of Human Resources services in Karang Sidemen Village is still minimal, especially Pokdarwis as a tourism driver. The purpose of this study is to describe the optimization of the role of Pokdarwis as an effort to manage the ecotourism potential of Karang Sidemen Village. The method used in this research is a qualitative approach. Qualitative narrative is obtained from field research. Data collection techniques by means of observation, interviews, and documentation. The data analysis technique used is SOAR analysis. Based on the research conducted, the results obtained are strategies for optimizing the role of Pokdarwis Selendang Biru Rinjani as an effort to manage ecotourism potential in Karang Sidemen Village, including conducting service quality training for Pokdarwis members, collaborating with well-known social media to promote promotions, collaborating to apply seven categories of assessment in ADWI regularly participates in various trainings outside of Pokdarwis, and optimizes Karang Sidemen Village in holding the title of Tourism Village.